Shifting Administrative Burden to the State: The Case of Medicaid Take‐Up. (20th August 2013) - Herd, Pamela; DeLeire, Thomas; Harvey, Hope; Moynihan, Donald P.
<x xml:space="preserve">Abstract</x> Administrative burden is an individual's experience of policy implementation as onerous. Such burdens may be created because of a desire to limit payments to ineligible claimants, but they also serve to limit take‐up of benefits by eligible claimants. For citizens, this burden may occur through learning about a program; complying with rules and discretionary bureaucratic behavior to participate; and the psychological costs of participating in an unpopular program. Using a mixed‐method approach, the authors explain process changes that reduced individual burden and demonstrate how this resulted in increased take‐up in Medicaid in the state of Wisconsin. The findings inform the planned expansion of Medicaid under the Patient Protection and Affordable Care Act. A key design principle for Medicaid and other means‐tested programs is that it is possible to increase program take‐up while maintaining program integrity by shifting administrative burdens from the citizen to the state.